Tight binding enantiomers of pre-clinical drug candidates. Issue 17 (1st September 2015) - Evans, Gary B.; Cameron, Scott A.; Luxenburger, Andreas; Guan, Rong; Suarez, Javier; Thomas, Keisha; Schramm, Vern L.; Tyler, Peter C.
Graphical abstract: Abstract: MTDIA is a picomolar transition state analogue inhibitor of human methylthioadenosine phosphorylase and a femtomolar inhibitor of Escherichia coli methylthioadenosine nucleosidase. MTDIA has proven to be a non-toxic, orally available pre-clinical drug candidate with remarkable anti-tumour activity against a variety of human cancers in mouse xenografts. The structurally similar compound MTDIH is a potent inhibitor of human and malarial purine nucleoside phosphorylase (PNP) as well as the newly discovered enzyme, methylthioinosine phosphorylase, isolated from Pseudomonas aeruginosa . Since the enantiomers of some pharmaceuticals have revealed surprising biological activities, the enantiomers of MTDIH and MTDIA, compounds1 and2, respectively, were prepared and their enzyme binding properties studied. Despite binding less tightly to their target enzymes than their enantiomers compounds1 and2 are nanomolar inhibitors.